An enhancement of bandwidth in patch antenna using metamaterial / Adib Othman - Othman, Adib (2009)
This project proposed a new generation of antenna that applies metamaterial as based construction of the antenna. Current bulky size antenna can easily be replaced by invented metamaterial antenna. The simulations of the metamaterial antenna as substrate have positive results with respect to the bandwidth and size of the antenna, while metamaterial antenna as cover also have positive results with respect to the bandwidth and directivity of the antenna. The omega structure was made of combination of two materials; Flame Retardant 4 and Perfect Electric Conductor which this design's resulting the formation of metamaterial. An investigation of the S-parameters has been carried out in determining the negative permittivity of this newly produced metamaterial. The return loss from the simulated metamaterial antenna as substrate is almost similar to the conventional antenna. Directivity of the conventional antenna was improved significantly with the use of metamaterial slab as cover of the antenna. The antennas lead to enhancing the technology to ease the customers by giving a smaller, cheaper and better performance of device.